Spaece: the materialization of external evaluation in the literacy cycle in Ceará - Lira, Lisiane Maria Abreu Martins (2024)
The article aims to problematize external evaluation in Brazilian education, and in particular, the Ceará-Spaece Permanent Basic Education Evaluation System. In this way, the text highlights the political context in which this control policy arrived in Brazil. Furthermore, this work discusses the historical process of implementing Spaece in the state of Ceará, and the objectives prescribed in the Spaece-alfa guidelines. By identifying the characteristics of the evaluation system of basic education in Ceará, this essay considers from a critical perspective the implications of this external examination in educational practice to reflect on the contours of this evaluation instrument expressed in everyday school life. The research seeks to question the intentionality of this evaluation in terms of improving education, as it compromises the teacher/student relationship and the construction of knowledge by mechanizing pedagogical practice to achieve goals.